Estrutura da Camada Limite Atmosférica Acoplada a Heterogeneidade Superficial no Sul da Amazônia – Experimento - Kaufmann, Thomas; Fisch, Gilberto (Ciência e Natura, 2013)
This study used dropsonde data from the SAMBBA field campaign (held during September/October 2012) in Amazonia. Preliminary results showed a remarkable evolution of the convective boundary layer (CBL) along surface heterogeneity, and in the presence of clouds.